In Vitro Assessment of the Fracture Resistance of Different Prosthodontic Materials for Fixed Dental Prostheses - Sherif El Sayed Sultan; Nawaf Hussain Saif Almuhyi; Khalid Maziad Alzabni; Rayan Hamad Qubayl Alruwaili (Wolters Kluwer Medknow Publications, 2024)
Background: Fixed dental prostheses (FDPs) are commonly used in prosthodontics to restore missing teeth and improve oral function and esthetics. The selection of prosthodontic materials significantly impacts the fracture resistance of FDPs, thus influencing their clinical success. This study aimed to assess the fracture resistance of different prosthodontic materials commonly used in FDPs through in vitro testing. Materials and Methods: Thirty standardized FDP specimens were fabricated using three different materials: Monolithic zirconia, heat press lithium disilicate, and metal ceramic. Each group consisted of ten specimens. The specimens were subjected to standardized loading using a universal testing machine until fracture occurred. Fracture resistance values were recorded in Newtons (N) and statistically analyzed using one-way analysis of variance (ANOVA) followed by post-hoc Tukey tests. Results: The mean fracture resistance values for the three materials were as follows: zirconia, 1450 N; lithium disilicate, 1200 N; and metal ceramic, 950 N. Statistical analysis revealed a significant difference among the groups (P < 0.05). Post hoc Tukey tests indicated that zirconia exhibited significantly higher fracture resistance compared to lithium disilicate and metal ceramic (P < 0.05). However, there was no significant difference in fracture resistance between lithium disilicate and metal-ceramic groups (P > 0.05). Conclusion: Within the limitations of this in vitro study, zirconia demonstrated the highest fracture resistance among the tested materials for FDPs, followed by lithium disilicate and metal ceramic. The findings highlight the importance of material selection in achieving optimal clinical outcomes and longevity of fixed dental prostheses.